Monosomal karyotype improves IPSS‐R stratification in MDS and AML patients treated with Azacitidine. Issue 9 (23rd July 2013) - Cluzeau, Thomas; Mounier, Nicolas; Karsenti, Jean‐Michel; Richez, Valentine; Legros, Laurence; Gastaud, Lauris; Garnier, Georges; Re, Daniel; Montagne, Nathalie; Gutnecht, Jean; Gabriel Fuzibet, Jean; Auberger, Patrick; et al.
<x xml:space="preserve">Abstract</x> IPSS‐R classifies cytogenetic abnormalities into five prognostic groups for survival. Monosomal karyotype (MK) is not a subgroup of IPSS‐R. Additional prognostic information from MK in poor and very poor karyotype has been recently shown. The aim of our study was to determine the prognostic value of IPSS‐R and MK for response and survival in AZA‐treated high‐risk MDS and AML with 20–30% of blasts patients. The study population included 154 patients who were classified according to IPSS‐R. IPSS‐R was not predictive of response (intermediate, 64%; poor, 44%; very poor, 56%; P = 0.28) or survival (intermediate, 25 months; poor, 12 months; very poor, 11 months; P = 0.14). Twenty‐one patients (15%) presented with MK and had a median OS of 9 months. Patients with a very high IPSS‐R score without MK had a median OS of 15 months, while patients with a high IPSS‐R score without MK had a median OS of 13 months (P = 0.18). We reclassified patients into the following three groups to include MK status: very high (MK only; OS median: 9 months), high (very high IPSS‐R without MK and high IPSS‐R without MK; OS median: 14 months) and intermediate (OS median: 25 months). As in recent publication including MK prognostic, we confirmed that this classification was predictive for survival in AZA treated patients (P = 0.008). IPSS‐R failed to discriminate between the prognostic subgroups. Stratification with MK has value in the prognosis of our cohort of AZA‐treated patients. Am. J. Hematol. 88:780–783, 2013. © 2013 Wiley Periodicals, Inc.